Severe malaria and death risk factors among children under 5 years at Jason Sendwe Hospital in Democratic Republic of Congo - Augustin Mulangu Mutombo; Olivier Mukuku; Kristel Nzeba Tshibanda; Edouard Kawawa Swana; Eric Mukomena; Dieudonné Tshikwej Ngwej; Oscar Numbi Luboya; Jean-Baptiste Kakoma; Stanislas Okitotsho Wembonyama; Jean-Pierre Van Geertruyden; Pascal Lutumba (The Pan African Medical Journal, 2018)

(untitled)
INTRODUCTION: Malaria is still a major public health concern in the Democratic Republic of Congo. Its morbidity and mortality challenge the actual strategies of the fight agains malaria. This study was aimed to describe the epidemiology, the clinical caracteristics and the risk factors of death associated to severe malaria in the pediatric population under 5 years at Sendwe Hospital of Lubumbashi. METHODS: this analytical retrospective study was conducted in Lubumbashi, in the province of Haut-Katanga. All patients under 5 years hospitalized for severe malaria were registered from January 2014 to December 2016. RESULTS: among the 3,092 patients hospitalised during our study period, 452 (14.6%) were admitted for severe malaria. The average age was 27.04 months, the male sex was the most affected (53.54% with the sex-ratio 1.15). The most frequent forms of gravity noticed were cerebral malaria (48.23%) and severe anemia (46.90%). Death was noted in the evolution in 28.32%. Repeated convulsion (OR = 2.27; 95% CI: 1.47-3.48), coma (OR = 3.55; 95% CI: 2.19-5.74) and severe acute malnutrition (OR = 3.32; 95% CI: 1.56-7.06) were asscociated with a high risk of death. CONCLUSION: this research shows that severe malaria is still an important cause of morbidity and mortality among young children in Lubumbashi. Neurologic and anemic forms are the most frequent. The predictive signs of death are: repeated convulsions, coma and severe acute malnutrition.